Dưới mắt tôi phê bình văn học Việt Nam hiện đại - Trương Chính 1916-2004 (H. Hội nhà văn, 2016)
Nhất Linh, Khái Hưng, Nguyễn Công Hoan, Vũ Trọng Phụng, Lê Văn Trương, Trương Tửu, Thạch Lam, Lan Khai, Nguyễn Khắc Mẫn, Nguyên hồng, Song An Hoàng Ngọc Phách, Từ Ngọc
Keywords: Văn học Việt Nam -- Phê bình -- 1930-1945; Phê bình văn học